2002
DOI: 10.1074/jbc.m203215200
|View full text |Cite
|
Sign up to set email alerts
|

ANGPTL3 Decreases Very Low Density Lipoprotein Triglyceride Clearance by Inhibition of Lipoprotein Lipase

Abstract: KK/San is a mutant mouse strain established in our laboratory from KK obese mice. KK/San mice show low plasma lipid levels compared with wild-type KK mice despite showing signs of hyperglycemia and hyperinsulinemia. Recently, we identified a mutation in the gene encoding angiopoietin-like protein 3 (Angptl3) in KK/ San mice, and injection of adenoviruses encoding Angptl3 or recombinant ANGPTL3 protein to mutant KK/San mice raised plasma lipid levels. To elucidate the regulatory mechanism of ANGPTL3 on lipid me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
264
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(273 citation statements)
references
References 34 publications
7
264
2
Order By: Relevance
“…Shimizugawa et al reported that VLDL secretion was normal in Angptl3 −/− mice (8). However, those studies were performed in fasted animals, when the effects of ANGPTL8 would be least apparent, whereas our studies were performed at the end of the dark cycle in food-replete animals.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Shimizugawa et al reported that VLDL secretion was normal in Angptl3 −/− mice (8). However, those studies were performed in fasted animals, when the effects of ANGPTL8 would be least apparent, whereas our studies were performed at the end of the dark cycle in food-replete animals.…”
Section: Discussionmentioning
confidence: 48%
“…Both ANGPTLs inhibit LPL (6)(7)(8). Overexpression of either protein inhibits LPL activity and causes hypertriglyceridemia, whereas loss-of-function mutations lead to very low TG levels (7,8).…”
mentioning
confidence: 99%
“…The low plasma triglyceride levels are possibly due to elevated lipoprotein lipase activity, which was reported to be inhibited by ANGPTL3 in vitro, whereas the low plasma free fatty acid levels may be connected to the impaired stimulatory effect of ANGPTL3 on adipose tissue lipolysis (21,22). Similar to ANGPTL3, there is evidence that FIAF also may inhibit lipoprotein lipase activity and hereby influence plasma levels of triglycerides (18,23), thus connecting FIAF to lipid metabolism.…”
mentioning
confidence: 89%
“…ANGPTL3 is expressed almost exclusively in the liver (5,6), and is only modestly regulated by food intake (12). Angptl3 −/− mice have increased LPL activity (8,13,14), and recombinant ANGPTL3 inhibits LPL in vitro (6,13,15,16), leading several investigators to propose that ANGPTL3 raises plasma TAG levels by inhibiting LPL activity (13,14). However, the concentrations of ANGPTL3 used in these studies were supraphysiological.…”
mentioning
confidence: 96%